Discourse Analysis of Argumentation from an English/Arabic Translation Perspective - Eisa, Sumaya Adam (2008)
A Master of Arts Thesis in Translation by Sumaya Adam Eisa Entitled, "Discourse Analysis of Argumentation from an English/Arabic Translation Perspective," June 2008. Available are both Hard and Soft Copies of the Thesis.